2015
DOI: 10.1093/jxb/erv042
|View full text |Cite
|
Sign up to set email alerts
|

Liming can decrease legume crop yield and leaf gas exchange by enhancing root to shoot ABA signalling

Abstract: HighlightThis paper describes a novel mechanistic understanding of how recommended rates of liming to manage soil pH may cause reduced gas exchange and growth in legumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
2
11
1
1
Order By: Relevance
“…Contrary to previous studies where limited P increased [ABA] leaf (Jeschke et al ; Rothwell et al ), we found that low P decreased [ABA] leaf and [ABA] xylem in all graft combinations (Figure ), which may result from changes in ABA biosynthesis, degradation, or long‐distance transport (Jeschke et al ; Peuke ). The decreased root hydraulic conductance of P‐deprived plants (Radin and Matthews ) should decrease leaf turgor, thereby stimulating leaf ABA accumulation, but no change in Ψ leaf was detected in our study (Figure A).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to previous studies where limited P increased [ABA] leaf (Jeschke et al ; Rothwell et al ), we found that low P decreased [ABA] leaf and [ABA] xylem in all graft combinations (Figure ), which may result from changes in ABA biosynthesis, degradation, or long‐distance transport (Jeschke et al ; Peuke ). The decreased root hydraulic conductance of P‐deprived plants (Radin and Matthews ) should decrease leaf turgor, thereby stimulating leaf ABA accumulation, but no change in Ψ leaf was detected in our study (Figure A).…”
Section: Discussioncontrasting
confidence: 99%
“…Under both P treatments, the higher g s (and lower Ψ leaf ) of the flc self‐grafts suggests that g s regulates Ψ leaf (Figure A), as previously reported for these graft combinations (Dodd et al ) and for reciprocally grafted WT and strigolactone‐deficient tomato plants (Visentin et al ). Foliar ABA accumulation was previously reported to correlate with low‐P‐induced stomatal closure (Radin ; Rothwell et al ). Although [ABA] leaf determined the maximal g s (Figure C), we found that low P decreased g s and [ABA] leaf in all graft combinations involving flc as either the rootstock or the scion, suggesting that other phytohormones (Martínez‐Andújar et al ) mediate stomatal responses to P status.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Attenuation of liming-induced stomatal closure in the ABA-deficient wilty pea mutant (Rothwell et al 2015) suggests an important role for ABA in mediating stomatal responses of pea to changes in rhizosphere elemental status, requiring further studies in salinised plants. Nevertheless, distinguishing the relative importance of phytohormonal and nutritional effects on stomatal closure can be challenging (Rothwell et al 2015). Although increased shoot K + : Na + ratio in response to ACCdeaminase containing PGPR has been demonstrated previously .…”
Section: Discussionmentioning
confidence: 99%